Critical Discourse Analysis: Advice via Instagram Social Media Regional Heads in The Use of Technology in Public Education - Setiawan, Budhi; Saddhono, Kundharu; Rohmadi, Muhammad; Wardana, Muhammad Aditya Wisnu (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
The prevention of the Covid-19 pandemic which took place in early 2020 – 2022 made regional leaders disseminate information about preventing Covid-19 through their respective social media by relying on access to information technology and social media owned by regional leaders. This research aims to analyze critical discourse based on Teun van Dijk's method which is divided into microstructure, superstructure and microstructure aspects. The method used in this research is a qualitative descriptive method with the type of research in the form of library research or library research which focuses on documentary analysis which refers to on the Instagram posts of regional heads Wahidin Halim (Governor of Banten Province) @wh_wahidinhalim, Anies Baswedan (Governor of DKI Jakarta) @aniesbaswedan, Ridwan Kamil (Governor of West Java) @ridwankamil, Ganjar Pranowo (Governor of Central Java) @ganjar_pranowo, and Khofifah Indar Parawansa ( Governor of East Java) @khofifah.ip. The results of research in critical discourse analysis according to Teun A. Van Djik's model are divided into three aspects, namely macro structure, superstructure and micro structure. This aspect can be found in social media posts with the same pattern, so it can be concluded that the aspect of critical discourse analysis in Instagram posts during the Covid-19 pandemic was that regional heads (governors) gave recommendations and appeals to the public to comply with health protocols and reduce activities outside the home.